Embryo Biopsy for Aneuploidy Detection in the General Infertility Population - Kaser, Daniel J.; Ginsburg, Elizabeth S. (Seminars in Reproductive Medicine, 2014)
Since report of the first live birth following preimplantation genetic screening (PGS) in 1995, the procedure and available technologies for aneuploidy detection have rapidly evolved. Through these efforts, the biology of meiotic and mitotic segregation errors has been partially elucidated. A process that began with polar body biopsy and four-color fluorescence in situ hybridization to detect copy number in a limited number of chromosomes is now hardly recognizable: current molecular methods permit high-density screening of the entire human genome for copy number variants, structural rearrangements, microdeletions, and polyploids to a resolution of 35 kilobases in less than 48 hours. Indeed, with the advent of real-time quantitative analyses of ploidy status that allow same-day trophectoderm biopsy with fresh transfer of a euploid blastocyst, the future is bright for PGS. Questions remain about how best to safely offer this technology to patients, and which patients, if any, will benefit from routine biopsy. Herein, we will review the limited available evidence for application of PGS in the general infertility population as an adjunct method to optimize live birth rates.
Keywords: aneuploidy; comprehensive chromosome screening; fluorescence in situ hybridization; preimplantation genetic screening; trophectoderm biopsy